Quantitative easing auctions of Treasury bonds - Song, Zhaogang; Zhu, Haoxiang (Journal of Financial Economics, 2018)
The Federal Reserve uses (reverse) auctions to implement its purchases of Treasury bonds in quantitative easing (QE). To evaluate dealers’ offers across multiple bonds, the Fed relies on its internal yield curve model, fitted to secondary market bond prices. From November 2010 to September 2011, a one standard deviation increase in the cheapness of a Treasury bond (how much the market price of the bond is below a model-implied value) increases the Fed’s purchase quantity of that bond by 276 million and increases the auction costs on that bond by 2.6 cents per $100 par value, controlling for standard covariates. Our results suggest that the Fed harvests gains from trades by purchasing undervalued bonds, but strategic dealers extract some profits because the Fed’s relative values can be partly inferred from price data.